Lempu’ Na Getteng as a Footing For The Professionalism of an Auditor - Tenriwaru Tenriwaru; Rizkyah Herawaty; Edy Susanto (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Lempu’ na getteng which is a Bugis culture that aims to create humans who have the nature and attitude of being honest, firm and fearing God so this value has a very positive influence on the formation of the personality of each individual. This study was conducted to determine whether there is a relationship between the value of lempu’ nagetteng and the Code of Professional Ethics which is an indicator of an auditor being declared a professional. This study uses primary data obtained directly through direct interviews with several auditors at two Public Accounting Firm in Makassar City. The data collection method used is qualitative using an ethnographic approach. The research instruments that support this research are mobile phones, stationery and the researchers themselves. The results of this study indicate that if an auditor has met the criteria for lempu’ nagetteng, he has also reflected the professionalism stated in the Code of Professional Ethics.